On ?-deferred statistical convergence and strongly deferred summable functions - Et, Mikail; Baliarsingh, Pinakadhar; Kandemir, Hacer Sengul; Kucukaslan, Mehmet (Springer-Verlag Italia Srl, 2021)
In this paper we introduce the concepts of strongly deferred Cesaro summable and mu -deferred statistical convergence of real-valued functions x=x(t) which are measurable (in the Lebesgue sense) in the interval [1,infinity). In addition, the relations between the set of strong deferred Cesaro summable and mu -deferred statistical convergent of functions have been examined under some restrictions.
Keywords: Statistical convergence; mu-deferred Statistical; Measurable function; Deferred Cesaro mean; mu-deferred statistical convergence; 40A05; 40C05; 46A45